Pendidikan Inklusif Berbasis Nilai Kasih dalam Perspektif Pendidikan Agama Kristen - Yitra Gloria Bana; Santi Aplunggi; Yentro Kurnyatu Djo; Priska Leo; Marwina Almet; Adriana Indra Santi Sole (INDO PUBLISHING, 2026)
Inclusive education is an educational paradigm that emphasizes the acceptance of every student without discrimination, including those with special needs. The value of love in Christian Religious Education (CRE) has profound relevance as a theological and pedagogical foundation for the implementation of inclusive education. This study aims to examine the relationship between the value of love in Christian teaching and the principles of inclusive education, as well as how CRE can serve as a transformative foundation for teachers, schools, and faith communities. The method used is library research with a descriptive qualitative approach. The results show that the value of love taught in the Bible provides a solid foundation for inclusive education, encompassing acceptance, empathy, justice, and boundless service. CRE grounded in love is capable of forming an inclusive learning community that values diversity and views every individual as the image of God. These findings indicate the urgency of integrating Christian love values into curriculum and pedagogical practices to create an inclusive, dignified, and transformative educational ecosystem.